Differentiation of Phaseolus vulgaris L. cultivars by leaf tissue response exposed to drought and salinity stress - Raúl Collado; Annerys Carabeo Pérez; Ivian Poveda Martínez; Luis E. Rojas; Michel Leiva-Mora; Lourdes R García; Novisel Veitía; Amanda Martirena; Damaris Torres; Leonardo Rivero (Biotecnología Vegetal, 2017)
The identification of Phaseolus vulgaris L. cultivars capable to tolerate abiotic stress without affecting its yield is a purpose of the breeding programs of this legume. The objective of this work was to differentiate P. vulgaris cultivars by the foliar tissue response exposed to hydric and saline stress in vitro induced. Leaf discs of 'Cuba Cueto 25-9 Negro' cultivar were placed in Petri dishes on filter paper. On each plate 2 ml of 6, 8, 10, 12, 14, 16 and 18% (w / v) PEG 6000 or 50, 100, 150, 200, 250, and 300 mM NaCl solution were added to induce hydric or saline stress. Deionized water was used as the control. The plates were maintained for 48 h at 25 ± 2 ° C. A scale of degrees of affectation was elaborated according to the percentage of foliar area with necrosis. In ten cultivars of P. vulgaris the assay was applied and its response recorded by the elaborated scale. Leaf tissue at 48 h showed necrotic areas. The designed scale was structured with seven grades where grade 1 corresponded with unaffected tissue and seven with tissue with total necrosis. The predominance of grade 3, 4 and 5 was observed. The response of cultivars exposed to PEG 6000 and NaCl was influenced by the type of stressor and it was classified as high, intermediate or low. The test of P. vulgaris leaf discs subjected to in vitro induced hydric and saline stress allows differentiation of the response of cultivars to these conditions through an elaborated qualitative scale based on the percentage of area with necrosis.